ANALISIS SWOT INDUSTRI ANYAMAN PANDAN SAKAYAN KAMPUNG LUBUK SARIAK NAGARI KAMBANG UTARA KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Wilis, Ratna; Rianto, Slamet; U, Iswandi (Pendidikan Geografi, 2013)
Small industry is a business skill that contain economic values, cultural values, and the value of art in society and should be preserved. Lengayang districts are districts in the South Coast and is one area that has many industrial enterprises, one of which is the famous hometown Sariak Lubuk with woven Pandan sakayan. This study aimed to obtain information, analyze industry SWOT woven pandanus sakayan Kampung Lubuk Sariak Nagari Kambang Lengayang Coastal District Northern District Southern views of : 1) strength, 2) weakness, 3) opportunities, 4) threat and 5) development strategy.This research is a qualitative study, carried out in Kampung Lubuk Sariak kanagarian North Kambang sub Lengayang South Coastal district. Research informants numbered 25 people. Data retrieved through observation and interviews.Research results showed: (1) The power possessed by sakayan woven pandanus pandanus is the availability of raw materials and close to many industrial sites, the attention of the government through the provision of capital, human resource development and workforce training. (2) owned by the weakness of woven pandanus sakayan is the capital needed to develop a large business, labor master woven in the group number is less, still not optimal marketing. (3) Opportunities owned by woven pandanus sakayan is the promotion of the local government so that products known by the public, the market demand is quite high and pretty much in demand by consumers, unique and interesting shape. (4) Threat of woven pandanus owned sakayan is the existing workforce so that parents are less productive, can not meet production targets if the market demand and marketing of the product is slow. (5) development strategy that is woven pandanus sakayan increase the amount of capital so as to develop products, raw materials and keep adding new raw materials, manpower training to improve skills, increase the number of members, making the store a strategic place.